F. Nietzsche‘s Conception of Perspectivism - Mickevičius, Arūnas (Problemos, 2004)
The article deals with F. Nietzsche's critical attitude to classical conception of truth and knowledge which is based on one and unique perspective to the world. Nietzschean conception of perspectivism says that during knowledge there is no universal true but only different interpretations of the world which are not adequate to it. In the article attempt to prove is done that the conception of perspectivism is ambiguous and inconsistent because it is based an knowledge unattainable and lost “truth”. This “truth” is negative and can be explicated only through trace. Given extra-perspective position allows us to speak about adequacy of the world and knowledge only using a word “as if”.
Keywords: power; interpretation; perspectivism; mask; face; trace; truth